A framework for assessing the potential for a double dividend from a policy-induced reduction in alcohol consumption on the economy. (May 2023) - Sachdev, R.; Roy, G.; Allan, G.
Abstract: Objectives: Tax policies targeted at reducing alcohol consumption are typically understood to be associated with economic losses, including in alcohol production and trade sectors. This study sought to determine whether the overall effect of reduced alcohol consumption might be positive once improvements in productivity associated with reduced alcohol-related consumption are considered. Study design: This study used Computable General Equilibrium economic modelling. Methods: An economic modelling framework was developed for Scotland, which considered the fiscal and economic impacts of alcohol taxation and the economy-wide impacts. Simulation of hypothetical alcohol taxes and improvements in labour productivity calibrated on losses due to absenteeism and presenteeism in Scotland in 2017. Results: The long-run impacts of a five pence increase in taxation alone produce negative economic impacts on jobs and Gross Domestic Product in Scotland (1189 jobs and £71.12 million). These effects are reduced by half – but remain negative – when the revenues from such policy are recycled to the economy through government spending. A small improvement in labour productivity – equivalent to 4.95% of the total productivity gap from absenteeism and presenteeism estimated for Scotland – would be sufficient to turn the economic consequence non-negative. Conclusions: The overall macroeconomic impact of policies targeted at alcohol consumption should include consideration of the potential productivity effect and that impact studies that do not include such mechanisms are likely to overstate the negative economic impacts of alcohol policies.